Cationic Polymers Inhibit the Conductance of Lysenin Channels - Daniel Fologea; Eric Krueger; Steve Rossland; Sheenah Bryant; Wylie Foss; Tyler Clark (The Scientific World Journal)
The pore-forming toxin lysenin self-assembles large and stable conductance channels in natural and artificial lipid membranes. The lysenin channels exhibit unique regulation capabilities, which open unexplored possibilities to control the transport of ions and molecules through artificial and natural lipid membranes. Our investigations demonstrate that the positively charged polymers polyethyleneimine and chitosan inhibit the conducting properties of lysenin channels inserted into planar lipid membranes. The preservation of the inhibitory effect following addition of charged polymers on either side of the supporting membrane suggests the presence of multiple binding sites within the channel's structure and a multistep inhibition mechanism that involves binding and trapping. Complete blockage of the binding sites with divalent cations prevents further inhibition in conductance induced by the addition of cationic polymers and supports the hypothesis that the binding sites are identical for both multivalent metal cations and charged polymers. The investigation at the single-channel level has shown distinct complete blockages of each of the inserted channels. These findings reveal key structural characteristics which may provide insight into lysenin’s functionality while opening innovative approaches for the development of applications such as transient cell permeabilization and advanced drug delivery systems.